Identity of north African endemic bryophytes, 3, with special emphasis in Funaria altissima - Ros Espín, Rosa María; Muñoz, Jesús; Werner, Olaf (Mediterranean Botany, 2023)
The types of five taxa described with material from northern Africa have been revised, yielding the following results: Barbula commutata var. erosa Corb. is synomyzed with Streblotrichum convolutum var. commutatum; Bryum trabutii Thér. with Ptychostomum rubens; Thamnium alopecurum var. decipiens Corb. with Scorpiurium circinatum; and Trichostomum mediterraneum var. algeriae Müll. Hal. ex Geh. with Hydrogonium bolleanum. Funaria altissima Dixon is recognized as a distinct species, for which we provide a full description, photographs, and a key to the more closely species. Lectotypes have been designated for all names except for F. altissima. The identity of two nomina nuda is also resolved: Funaria hygrometrica var. dentata Corb. ex Maire & Werner, corresponds to typical Funaria hygrometrica, and Zygodon dimorphus Thér. ex Jelenc is here identified as Grimmia torquata¸ an interesting addition to the bryophyte flora of Morocco and continental Africa. Ptychostomum rubens is reported for the first time from Algeria.